Analisis Penerapan Akuntansi Syariah Pada Skema Jual Beli KPR Syariah - Sholikah, Mar’atus; Isharijadi, Isharijadi; Astuti, Elly (Universitas Muhammadiyah Yogyakarta, 2020)
This study aims to analyze the application of Islamic accounting in the Islamic credit buying and selling scheme in housing sales at PT MIB and to find out the Islamic law review related to the difference in cash prices and credit prices that have been included in the sales brochure whether there is an element of usury or not. This type of research uses a qualitative study with a descriptive approach. The data sources used are primary data sources and secondary data sources. Data collection techniques using observation, interviews, and documentation. This study uses the triangulation of sources. Data analysis techniques are data collection, data reduction, data presentation, and data verification. The results of PT MIB's research use alternative economic and inflation methods. Based on PSAK 102 Accounting for murabahah and ISAK 101 regarding the recognition of tough murabahah income without any significant risks related to inventory ownership, the use of both methods is permitted. Based on this method, it is time that has economic value so that when there is a deferral of payments, a certain amount of compensation is needed because basically money is the medium of exchange for the public. The faster the rotation, the better. Credit buying and selling mechanism is also allowed in the Qur'an, Hadith, and Ijma.